34. QUALITY OF LIFE IN STROKE PATIENTS WITH PARALYSIS AT HA TINH REHABILITATION HOSPITAL IN 2024 (Tạp chí Y học Cộng đồng, 2024)
Background: Stroke is a major health concern globally due to its high mortality and long-term disability impacts, significantly affecting the quality of life of survivors. This study aims to assess the QoL of stroke patients with paralysis at Ha Tinh Rehabilitation Hospital in 2024, focusing on physical, functional, psychological, and social aspects.Methods: A cross-sectional descriptive study was conducted from April to October 2024 at Ha Tinh Rehabilitation Hospital. Data were collected through interviews using the Stroke-Specific Quality of Life tool. A total of 103 stroke patients with paralysis were included in the study. Descriptive statistics and SPSS version 25.0 were used for data analysis.Results: The average quality of life score of the patients was 114.83, indicating a moderate level of quality of life. The majority of patients (59.2%) had moderate quality of life, 37.9% had poor quality of life, and only 2.9% reported good quality of life. Physical and functional health scores were relatively low, especially in energy and work/productivity domains, while psychological and social factors also presented challenges.Conclusion: The study highlights that most stroke patients with paralysis experience moderate to poor quality of life. These results emphasize the need for comprehensive rehabilitation programs that address not only physical recovery but also psychological support and social reintegration, especially in rural areas like Ha Tinh.
Keywords: Stroke; Quality of Life; Paralysis; SS-QOL; Ha Tinh Rehabilitation Hospital